Gambaran Pengetahuan Ibu Hamil tentang Kekurangan Energi Kronis (KEK) di Puskesmas Pahandut Kota Palangka Raya - Angga Arsesiana; Ni Kadek Diah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The nutritional status of pregnant women dramatically affects the growth of the fetus in the womb. In Central Kalimantan alone, the number of pregnant women with chronic energy deficiency is still high, seen from the upper arm circumference measurement of pregnant women in the health profile of Central Kalimantan Province in 2017. The purpose of this study was to find out the level of knowledge of pregnant women about Chronic Energy Deficiency at the Pahandut Health Center, Palangka Raya City. This research design uses a descriptive research design. The sampling method used is Nonprobability Sampling (Accidental Sampling). Samples were taken from as many as 32 respondents, namely all pregnant women. The research data was taken using a questionnaire. The results showed that the knowledge of pregnant women about Chronic Energy Deficiency (KEK) was categorized as lacking in as many as 22 respondents (69%), adequate knowledge among as many as seven respondents (22%), and three respondents with good knowledge (9%). Most pregnant women have less knowledge; this is due to the lack of information from the media that explains the nutritional intake of pregnant women.